Summerland [compact disc, unabridged] : a novel - Hilderbrand, Elin (Hachette Audio, 2012)
On the night of high school graduation, Jake Randolph survives a car crash that kills his girlfriend and leaves her brother in a coma. Jake and his family move to the west coast of Australia in order to escape the horrors of the accident. Demeter Castle, another survivor of the crash, falls prey to alcohol abuse and other self-destructive behaviors that nearly lead to her destroying her own life.